Clinical to Molecular Screening Paradigm for β-Thalassemia Carriers. (August 2015) - Abdel-Messih, Ibrahim Y.; Youssef, Soha R.; Mokhtar, Galila M.; Elmogy, Mahira I.; Mahmoud, Hanan M.; Ayoub, Mariz; Pessar, Shaimaa A.
Abstract β-Thalassemia (β-thal) represents a major health problem worldwide and particularly in Egypt. Its prevention, compared to treatment, is cost-effective, possible and practical. In this study we evaluate a proposed paradigm for detection of the β-thal carrier state. The present study included 1627 children and adolescents of both sexes, presenting as outpatients to clinics of Ain-Shams University Hospitals, Cairo, Egypt, from November 1 2009 to June 30 2010. In the first phase, after performing a complete blood count (CBC), 280 microcytic hypochromic patients were selected. These cases were further analyzed by iron profile and high performance liquid chromatography (HPLC); in the second phase, hybridization detected 22 common β-globin mutations in 74.0% of the suspected cases. Thus, by HPLC, the Hb A2 level of >3.5% provided 100.0% sensitivity, 70.0% specificity, 75.0% positive predictive value (PPV), 100.0% negative predictive value (NPV) and accuracy of 70.0% to identify β-thal trait and at a cut-off of 4.0%, it provided 97.4% sensitivity, 72.7% specificity, 92.6% PPV, 88.8% NPV and a diagnostic accuracy of 92%. High performance liquid chromatography is a reliable and cost effective primary screening tool for β-thal trait at a Hb A2 level of ≥4.0%, while molecular testing is mandatory only for selected cases with borderline Hb A2 values between 3.5 and 4.0%.